Qualidade de água para consumo humano e saúde ambiental no Projeto de Assentamento Nova Amazônia, Boa Vista-Roraima - Nascimento, Priscila da Silva (2022)
The Settlement Project Nova Amazônia - PANA, is a rural settlement, located in the gleba Cauamé in Boa Vista-RR, where families develop, for the most part, family agriculture. This settlement does not have access to water supply, sewage collection, and solid waste services. As an alternative, families use wells and some forms of water treatment and strategies to ensure environmental health and environmental and socioeconomic indicators can point out the weaknesses or efficiency of these alternatives. The objective of this research was to determine the quality of water for human consumption in the PANA poles; to relate the health of the environment to the health conditions of the families and, to point out the indicators of environmental health. Water samples were randomly collected from households in the dry and rainy periods and followed the Standard Methods for the Examination of Water and Wastewater. The environmental health and the families' perceptions were collected through semi-structured questionnaires, dialogues, and on-site observations. Fifty-two families participated in the research, corresponding to 10% of the families occupying plots in each pole. The results showed that the PANA waters are inadequate for human consumption, since 100% of the analyzed samples showed contamination by total coliforms in the five poles, 78% of them with heterotrophic bacteria counts above 500 CFU/ml and 97% of the samples showed E. coli, especially in the rainy season; the presence of chlorine was not detected in any of the analyzed samples in the five poles. 383.2 hardness was found in the dry season in pole I and 480.4 in pole III. Most families have good hygienic-sanitary practices according to knowledge passed from generation to generation and perceptions; the main environmental indicator was the quality of water resources, hygienic-sanitary practices. The most relevant socioeconomic indicators were mainly income and literacy, which showed a relationship with sanitary conditions. The most frequent waterborne diseases were allergies and diarrhea in adults and weight loss with food refusal and abdominal pain in children. Most families (79%) did not perceive any organoleptic alterations in the drinking water. The water from the wells studied is unfit for human consumption and anthropic action is one of the main generators of environmental imbalance in the PANA with consequences on the health of families. The data from this study can contribute to the understanding of the environment-health-disease process and how it relates to the migration process and the environment, contributing to the construction of public policies aimed at environmental sustainability and the well-being of families.